Dynamic System Identification and State Evaluation - Gaofeng, Zhou; Qi, Zhang (Modern Control Systems: Theory, Design and Applications, 2025)
This chapter mainly focused on dynamic system identification and state evaluation. Estimating the controller’s parameter or objective online became an important part of self-revision control. In a lot of fields of science and society, quantitative analysis and comprehensive design and predictive future action were both based on the dynamic characteristics of the system. Hence dynamic system identification and state evaluation were very helpful to implement adaptive control and other estimation or control.